2007
DOI: 10.1016/j.combustflame.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical kinetic considerations for postflame synthesis of carbon nanotubes in premixed flames using a support catalyst

Abstract: Multiwalled carbon nanotubes (MWCNTs) on a grid supported cobalt nanocatalyst were grown, by exposing it to combustion gases from ethylene/air rich premixed flames. Ten equivalence ratios (φ) were investigated, as follows: 1.37, 1.44, 1.47, 1.50, 1.55, 1.57, 1.62, 1.75, 1.82, and 1.91. MWCNT growth could be observed for the range of equivalence ratios between 1.45 and 1.75, with the best yield restricted to the range 1.5-1.6. A one-dimensional premixed flame code with a postflame heat loss model, including det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…Lumped cluster model -If CO reacts with metal clusters and removes atoms from them by forming MeCO, this has the effect of enhancing the evaporation rate and reducing SWCNT production [1] Iron catalyst chemistry in modeling a high-pressure carbon monoxide CNT reactor Gopinath and Gore (2007) [5] Gas-phase synthesis of SWCNTs on iron catalyst particles…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lumped cluster model -If CO reacts with metal clusters and removes atoms from them by forming MeCO, this has the effect of enhancing the evaporation rate and reducing SWCNT production [1] Iron catalyst chemistry in modeling a high-pressure carbon monoxide CNT reactor Gopinath and Gore (2007) [5] Gas-phase synthesis of SWCNTs on iron catalyst particles…”
Section: Referencesmentioning
confidence: 99%
“…Chemical kinetics considerations reported by Gopinath and Gore [5] for post-flame synthesis of CNTs in premixed flames using a support catalyst showed that the yield of multi-wall carbon nanotubes (MWCNTs) varied with the equivalence ratio of the fuel-air mixture. Chemical kinetics calculations also revealed that the gas phase mixture leading to CNT growth was not in partial equilibrium even for the water-gas shift reaction [87] .…”
Section: Referencesmentioning
confidence: 99%
“…Schematics of various flame synthesis processes are shown in figure 4. (Gopinath & Gore, 2007;Height et al, 2004;) (b) counter-flow diffusion flame (Li et al, 2007;Merchan-Merchan et al, 2003;)(c) co-flow diffusion flame Vander Wal, 2000;)(d) inverse diffusion flame (Lee et al, 2004;Unrau et al, 2007;Xu et al, 2006) In a flame, fuel (generally hydrocarbons such as methane (CH 4 ), ethylene (C 2 H 4 ), and acetylene (C 2 H 2 ) etc.) reacts with oxidizer (O 2 from air) to produce gaseous mixture that includes carbon dioxide (CO 2 ), water vapor (H 2 O), carbon monoxide (CO), hydrogen (H 2 ), saturated and unsaturated hydrocarbons(C 2 H 2 , C 2 H 4 , C 2 H 6 etc.)…”
Section: Experimental Investigationmentioning
confidence: 99%
“…The first evidence for filamentous carbon growth in flames was established using premixed flames (Singer & Grumer, 1959). In the last two decades premixed flat flames have been extensively studied for synthesis of carbon nanotubes (Diener et al, 2000;Gopinath & Gore, 2007;Grieco et al, 2000;Howard et al, 1992;Howard et al, 1991;. Formation of C60 and C70 fullerenes was first observed in premixed flames by Howard et al In their studies, sooty discharge from premixed laminar flames of benzene, oxygen and argon at low pressures (1.60 to 13.35 kPa) were analyzed using electron impact mass spectroscopy.…”
Section: Premixed Flame Synthesismentioning
confidence: 99%
See 1 more Smart Citation